Komparasi Manajemen Desain Lingkungan Pendidikan Anak Usia Dini di TK Ceria Timoho dan RA Sahabat Berbah - Rohmah, Lailatu (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2016)
At an institute of PAUD one of management that is important to be attentive is management design environment either a design the interior/indoor and outdoor/exterior. It is considering this institution is the protege on children in the golden age is the most rapid development of the brain. The kind of research this is qualitative and the data collection by interviews, documentation, and observation. Data analysis with a groove the reduction of the data, display data, and verification/conclusion. The results of research shows the management of environmental design early childhood education in TK Ceria and RA Sahabat been through the process of good management the planning, organizing, actuating and controlling. The environment for early childhood education facilities indoor and outdoor in TK Ceria had been optimal. RA Sahabat in learning more from the environment as a source of learning.